Rapid Truck Loading for Efficient Feedstock Logistics - Robert “Bobby” Grisso; John Cundiff; Subhash C. Sarin (AgriEngineering, 2021)
A multi-bale handling unit offers an advantage for the efficient hauling of round bales. Two empty racks on trailers are left at a satellite storage location for loading while a truck tractor delivers two loaded racks to the biorefinery, thus uncoupling the loading and hauling operations and increasing the efficiency of both. The projected 10 min trailer exchange time equals the projected 10 min unload time at the biorefinery achieved by lifting off the two full racks and replacing them with two empties, a technology adapted from the container shipping industry. A concept is presented for a bale loader that latches onto the rack/trailer and loads bales into the bottom tier chambers. This machine will load 10 bales into the rack on the front trailer by attaching on to the front of the trailer and 10 bales into the rear trailer by attaching onto the rear. A telehandler removes bales from single-layer storage and places them in the bale loader to load the bottom tier compartments. The top tier compartments are loaded directly from the top. Expectations are that an experienced operator can average 9 loads in a 10 h workday, and load-out cost is estimated as 3.61 USD/Mg, assuming the average achieved load-out productivity over annual operation is 60% of optimum productivity (24 Mg/h) equal to 14.4 Mg/h. Cost increases to 4.81 USD/Mg when the productivity factor drops to 45%, and cost is 3.09 USD/Mg for a factor of 70%.